Drought responses by individual tree species are not often correlated with tree species diversity in European forests. Issue 6 (26th July 2016) - Forrester, David I.; Bonal, Damien; Dawud, Seid; Gessler, Arthur; Granier, André; Pollastrini, Martina; Grossiord, Charlotte
Summary: Drought frequency and intensity are predicted to increase in many parts of the Northern Hemisphere and the effects of such changes on forest growth and tree mortality are already evident in many regions around the world. Mixed‐species forests and increasing tree species diversity have been put forward as important risk reduction and adaptation strategies in the face of climate change. However, little is known about whether the species interactions that occur in diverse forests will reduce drought susceptibility or water stress. In this study, we focused on the effect of drought on individual tree species ( n  =   16) within six regions of Europe and assessed whether this response was related to tree species diversity and stand density, and whether community‐level responses resulted from many similar or contrasting species‐level responses. For each species in each plot, we calculated the increase in carbon isotope composition of latewood from a wet to a dry year (Δδ 13 C) as an estimate of its drought stress level. When significant community‐level relationships occurred (three of six regions), there was only one species within the given community that showed a significant relationship (three of 25 species–region combinations), showing that information about a single species can be a poor indicator of the response of other species or the whole community. There were many two‐species mixtures in which both species were less water‐stressed compared with their monocultures, but also many mixtures where both species were more stressed compared with their monocultures. Furthermore, a given species combination responded differently in different regions. Synthesis and applications . Our study shows that drought stress may sometimes be reduced in mixed‐species forests, but this is not a general pattern, and even varies between sites for a given combination. The management or prediction of drought stress requires consideration of the physiological characteristics of the mixed species, and how this complements the water‐related climatic and edaphic features of the site, rather than species richness. Abstract : Our study shows that drought stress may sometimes be reduced in mixed‐species forests, but this is not a general pattern, and even varies between sites for a given combination. The management or prediction of drought stress requires consideration of the physiological characteristics of the mixed species, and how this complements the water‐related climatic and edaphic features of the site, rather than species richness.